2021
DOI: 10.3389/fpubh.2021.625523
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Outcomes of Healthcare Providers During COVID-19 Pandemic in Saudi Arabia: A Cross-Sectional Study

Abstract: Objective: In this descriptive cross-sectional study we aimed, to assess the level of depression, anxiety, insomnia and distress symptoms experienced by healthcare providers during the COVID-19 pandemic in Saudi Arabia.Methods: All healthcare providers currently working in different hospitals were invited to participate in this study. Data gathering started in March 2020 to May 2020. The participants answered a five-part questionnaire which includes demographic data, a 9-item Patient Health Questionnaire, a 7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
10
2
Order By: Relevance
“…Other studies ( 11 , 17 ) have reported similar findings of daily stress accumulation and consequential manifestation of psychological problems such as depressive symptoms, anxiety and other forms of mental discomfort, including suicidal ideation. Recent publications have documented that responding to the health needs of others during the pandemic has been consistently identified as a source of significant stress and a mental health challenge among HCWPs ( 1 , 12 ). Many HCWPs find it difficult to work under extreme pressures such as deciding how to allocate limited resources to equally needy patients, how to find a balance between their own mental health care needs and those of their clients, and how to align their duty to patients with their own personal responsibilities to family and friends ( 12 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies ( 11 , 17 ) have reported similar findings of daily stress accumulation and consequential manifestation of psychological problems such as depressive symptoms, anxiety and other forms of mental discomfort, including suicidal ideation. Recent publications have documented that responding to the health needs of others during the pandemic has been consistently identified as a source of significant stress and a mental health challenge among HCWPs ( 1 , 12 ). Many HCWPs find it difficult to work under extreme pressures such as deciding how to allocate limited resources to equally needy patients, how to find a balance between their own mental health care needs and those of their clients, and how to align their duty to patients with their own personal responsibilities to family and friends ( 12 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have documented that responding to the health needs of others during the pandemic has been consistently identified as a source of significant stress and a mental health challenge among HCWPs ( 1 , 12 ). Many HCWPs find it difficult to work under extreme pressures such as deciding how to allocate limited resources to equally needy patients, how to find a balance between their own mental health care needs and those of their clients, and how to align their duty to patients with their own personal responsibilities to family and friends ( 12 , 26 ). Listening to concerns and having compassion toward those more severely affected by the pandemic seems to lead to additional stress resulting in fear, anger, frustration, hopelessness, guilt, depression, and even suicidal ideation ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 This might indicate that Saudi Arabia has been effective in adopting mitigation strategies to prevent virus transmission, but not very effective in addressing the impact of COVID-19 on citizens' health and health care operations. For instance, less preference for physicians adopting telemedicine, 46 lack of proper management of work burden and stress on health care practitioners, 47 , 48 were few such issues that highlight the ineffectiveness of the strategies adopted. In this context, the impact of COVID-19 can be observed in areas related to access and administration, operations, and personalization in Europe, the Middle East, and African regions.…”
Section: Introductionmentioning
confidence: 99%